Economic performance of banks: A literature review - Nguyen , Tran Trung (Journal of Finance - Marketing Research, 2025)
This literature review provides an updated and comprehensive perspective on bank performance, which has been extensively explored for several decades but has gained even more attention in the wake of the global financial crisis. This paper builds on previous studies by including a more diverse set of countries and periods, which provides a fresh insight into changing patterns of bank performance in various contexts. Although profitability, efficiency, and stability are the three most important aspects of bank performance, empirical studies tend to focus only on the first two. In terms of methodologies, financial ratios, and frontier analysis continue to be widely used to assess bank performance. While financial ratios are mostly employed to assess bank profitability, frontier analysis is utilized for cost and profit efficiency calculations. Regarding frontier analysis, the Stochastic Frontier Approach is the most widely applied parametric method while Data Envelopment Analysis is acknowledged as the most common non-parametric method. There are similar and contrasting findings on factors determining bank performance, including bank-specific, industry-specific, macroeconomic and environmental, social, and governance factors. Overall bank performance and bank performance under economic crises also received a range of similarities and differences. It is argued that the rationale for this heterogeneity lies in the methodology used, chosen timeframes, and observed regions.